A new cryptic species of the pineapple fish genus Monocentris (Family Monocentridae) from the western Pacific Ocean, with redescription of M. japonica (Houttuyn, 1782) - Su, Yo; Lin, Hsiu-Chin; Ho, Hsuan-Ching (Zootaxa, 2022)
A new pineapple fish is described based on 26 type and 80 non-type specimens collected from Taiwan, Vanuatu, the Solomon Islands, and Queensland, Australia. This new species is sympatric with and similar to Monocentris japonica but can be distinguished from the latter in having only 6 or 7 scales on the third scale row below the lateral line; excisura notched and a small pseudo-excisura present on the sagittal otolith; consistently greater head depth, body depth, postorbital length, dorsal-fin–pelvic-fin length, and dorsal-fin–pectoral-fin length in proportion to standard length. A detailed description and designation of neotype are provided for M. japonica. DNA barcoding analysis supports the distinction of the new species with an estimated average COI gene divergence of 3.6 % from M. japonica.